PENILAIAN POTENSI DAN PERSEPSI PENGUNJUNG TERHADAP OBJEK DAYA TARIK WISATA ALAM DI DESA BARU KECAMATAN BATU BENAWA KABUPATEN HULU SUNGAI TENGAH - Noorlinda Novianty; Khairun Nisa; Asysyifa - (Jurnal Sylva Scienteae, 2021)
The potential for ecotourism is all tourist objects that require a lot of handling to provide an attractive value for tourists. Assessment of the potential and perception of visitors to the new Nature attraction objects is very influential for ecotourism development. The purpose of this research is to assess potential attraction objects and analyze visitor perception of the attraction of the Riam Bajandik and Pulau Mas attractions. The research method is an observation of tourist attractions by looking at the guide for Regional Analysis of Objects and Natural Tourism Attractions and interview methods. Determination of respondents using incidental sampling method with the number of respondents selected on the Riam Bajandik nature tourism is 40 people and the tourist attraction of Pulau Mas 50 people. The data analysis used is descriptive analysis and tabulation. The potential value of The Riam Bajandik tourism object is 486.67, while the potential value of The Pulau Mas tourism object is 491.67. The comparison of the potential value of the two tourist objects lies in their tourist attractiveness. From the results of the potential assessment, the two tourist objects have the potential to be developed. The perception of visitors to the two tourist objects is that visitors want improvements in infrastructure, increase management and visitor services, and add types of activities carried out.  Visitors give a pleasant impression when they are on both attractions and want to revisit both of these attractions. Keywords: Ecotourism; Tourism potentials; Perception of visitors